ORTA ÇAĞ’DA ‘KÖLELİK’ ÜZERİNE BİR DEĞERLENDİRME - ÖZDEMİR, Mehmet Nadir (e-Sarkiyat Ilmi Arastirmalari Dergisi, 2020)
The aim of this study was to determine the significance of slavery in the medieval world and address its economic, cultural, and religious repercussions from a human perspective. Cultures and people should not be discredited over past events, indicating that the history of the Muslim east should be addressed from the context of both the European and Arabian peninsula. In the medieval Europe, slave labor was replaced by a new style of workforce through changes in the production and class society structure. The factor giving rise to slavery in Europe was to utilize slaves' workforce while it was private service, trade, and other businesses in the Arabian Peninsula. In the post-Islamic period, the motivation behind slavery was prisoners of war, however, it was not easy for them to meet their needs and participate in social life. Incidents in those years caused positive and negative views to be recorded in terms of human rights. However, the Qur'an and hadiths do nor order to seize slaves. In fact, some verses and hadiths address the virtues of freeing slaves. Even though slavery ended through emancipation, Islam adopted different means of emancipation to eliminate slavery.
Keywords: 8. Economic growth; 16. Peace & justice